2007
DOI: 10.1007/s00381-007-0404-8
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation in children with refractory epilepsy: unusual complications and relationship to sleep-disordered breathing

Abstract: VNS appears to be an effective treatment for children with refractory epilepsy. Development of intractable cough in one patient in spite of device being turned off and recurrent infection-related removal in another are unusual complications. Polysomnography before implantation of VNS should be considered to identify patients with pre-existing OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 16 publications
2
53
0
Order By: Relevance
“…31 Khurana et al reported that tonsillectomy and adenoidectomy reduced seizure frequency by ≥ 50% in children with mild to moderate OSA after placement of a VNS. 17 Presumably reducing the number of apneas and hypopneas improved seizure control in this small group of patients. 17 In addition, a major treatment issue in these patients is CPAP compliance, especially in the pediatric population.…”
Section: Question 4: Does Intermittent Vagus Nerve Stimulation Increamentioning
confidence: 87%
See 3 more Smart Citations
“…31 Khurana et al reported that tonsillectomy and adenoidectomy reduced seizure frequency by ≥ 50% in children with mild to moderate OSA after placement of a VNS. 17 Presumably reducing the number of apneas and hypopneas improved seizure control in this small group of patients. 17 In addition, a major treatment issue in these patients is CPAP compliance, especially in the pediatric population.…”
Section: Question 4: Does Intermittent Vagus Nerve Stimulation Increamentioning
confidence: 87%
“…17 Presumably reducing the number of apneas and hypopneas improved seizure control in this small group of patients. 17 In addition, a major treatment issue in these patients is CPAP compliance, especially in the pediatric population. More prospective studies involving a larger number of patients are needed to determine whether VNS-induced apnea influences seizure control and/or quality of life in patients with epilepsy.…”
Section: Question 4: Does Intermittent Vagus Nerve Stimulation Increamentioning
confidence: 87%
See 2 more Smart Citations
“…Decreases in airflow and respiratory effort (and rarely, frank obstructive events) are observed during the 30-second period when the stimulator activates (typically every 5 minutes). These findings have been Primary Sleep Disorders in People with Epilepsy observed in adults [88][89][90] and children 66,68,[91][92][93][94][95] treated with the device. Most often, the respiratory change is an increase in the respiratory rate and decrease in respiratory amplitude when the device fires, which usually does not cause an arousal or desaturation.…”
Section: Recognizing the Effects Of Vagal Nerve Stimulation On Respirmentioning
confidence: 82%